On the Translation of Music Towards the Relation between Musikvermittlung and Innovation - Staples, Ronald (Transcript-Verlag, 2022)
If arts and artists are the societal experts for the creation of novelty and innovation as well as novelty are modern synonyms for societal progress, why do arts organisation need something like »Musikvermittlung«. This contribution tries to give an answer to this puzzling question by reconstructing art as a form of communication. It is argued that Musikvermittlung is an innovation of the arts system in order to translate the specifics of artistic communication.
CRIS-Team Scopus Importer:2022-10-28